Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1055/s-0036-1584901
|View full text |Cite
|
Sign up to set email alerts
|

A Case of True Brachial Artery Aneurysm with Severe Left Upper Limb Ischemia

Abstract: Upper extremity aneurysms are relatively rare compared with other peripheral arterial aneurysms, and most are false aneurysms.1 Especially, true brachial artery (BA) aneurysms are rare. Although the majority of the BA aneurysms are thought to be the result of trauma, 2 their natural history and incidence are still unclear. Case ReportAlthough a 65-year-old man underwent the creation of a radiocephalic arteriovenous fistula at the left wrist in 2004 at another hospital, the fistula was occluded and so he under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The pathological examination did not reveal typical arteriosclerotic change, but CT findings showed the severe arteriosclerotic change in the abdominal aorta, so it was very likely that the brachial artery got some arteriosclerotic effect and damaged. And more, Marconi et al [13] and Nishimura et al [14] reported true BAA located near the elbow like our case. Chronic mechanical stimulation, an elbow joint movement might also promote damages to the brachial artery.…”
Section: Discussionsupporting
confidence: 70%
“…The pathological examination did not reveal typical arteriosclerotic change, but CT findings showed the severe arteriosclerotic change in the abdominal aorta, so it was very likely that the brachial artery got some arteriosclerotic effect and damaged. And more, Marconi et al [13] and Nishimura et al [14] reported true BAA located near the elbow like our case. Chronic mechanical stimulation, an elbow joint movement might also promote damages to the brachial artery.…”
Section: Discussionsupporting
confidence: 70%
“…Rest pain and ulceration usually respond dramatically to revascularization. 10 However, recurrence of brachial artery aneurysm has also been reported. 11 Our case also responded considerably to treatment and the postoperative course was uneventful.…”
Section: Discussionmentioning
confidence: 99%